30-day mortality in patients hospitalized with COVID-19 during the first wave of the Italian epidemic: A prospective cohort study. (August 2020) - Giacomelli, Andrea; Ridolfo, Anna Lisa; Milazzo, Laura; Oreni, Letizia; Bernacchia, Dario; Siano, Matteo; Bonazzetti, Cecilia; Covizzi, Alice; Schiuma, Marco; Passerini, Matteo; Piscaglia, Marco; Coen, Massimo; et al.
Graphical abstract: Abstract: Italy was the first European country hit by the COVID-19 pandemic and has the highest number of recorded COVID-19 deaths in Europe. This prospective cohort study of the correlates of the risk of death in COVID-19 patients was conducted at the Infectious Diseases and Intensive Care units of Luigi Sacco Hospital, Milan, Italy. The clinical characteristics of all the COVID-19 patients hospitalised in the early days of the epidemic (21 February -19 March 2020) were recorded upon admission, and the time-dependent probability of death was evaluated using the Kaplan-Meier method (censored as of 20 April 2020). Cox proportional hazard models were used to assess the factors independently associated with the risk of death. Forty-eight (20.6 %) of the 233 patients followed up for a median of 40 days (interquartile range 33–47) died during the follow-up. Most were males (69.1 %) and their median age was 61 years (IQR 50–72). The time-dependent probability of death was 19.7 % (95 % CI 14.6–24.9 %) 30 days after hospital admission. Age (adjusted hazard ratio [aHR] 2.08, 95 % CI 1.48−2.92 per ten years more) and obesity (aHR 3.04, 95 % CI 1.42−6.49) were independently associated with an increased risk of death, which was also associated with critical disease (aHR 8.26, 95 % CI 1.41−48.29), C-reactive protein levels (aHR 1.17, 95 % CI 1.02−1.35 per 50 mg/L more) and creatinine kinase levels above 185 U/L (aHR 2.58, 95 % CI 1.37−4.87) upon admission. Case-fatality rate of patients hospitalized with COVID-19 in the early days of the Italian epidemic was about 20 %. Our study adds evidence to the notion that older age, obesity and more advanced illness are factors associated to an increased risk of death among patients hospitalized with COVID-19.